AB0344 Association between Red Blood Cells Distribution Width and Disease Activity Score in Rheumatoid Arthritis. (10th June 2014) - Calabria, M.; Bruno, C.; Tripolino, C.; Ursini, F.; Naty, S.; Grembiale, R.D.
Abstract : Background: Red blood cell distribution width (RDW) is a continuous measure representing the variability in size of circulating erythrocytes. This parameter has been independently associated with the risk of cardiovascular events and death. Previous studies found an interesting association between RDW and inflammatory indexes such as erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), in several pathological conditions. Although some investigations highlighted the role of RDW as a marker of disease activity in systemic lupus erythematosus or inflammatory bowel diseases, data are still lacking about a possible association with disease activity score (DAS 28) in rheumatoid arthritis (RA). Objectives: To investigate a possible correlation between RDW and DAS 28 in a cohort of RA patients. Methods: Subjects who met the ACR/EULAR criteria for rheumatoid arthritis attending the Rheumatology outpatient clinic – Internal Medicine Unit of University of Catanzaro were recruited for the present study. Exclusion criteria were: clinical conditions (i.e. anemia, infective disease, cancer) able to affect RDW and other hematological parameters. After excluding participants not fulfilling inclusion criteria, 66 subjects were recruited. Each patient underwent clinical examination and blood sampling. Serum hs-CRP level, ESR, hemoglobin concentration (Hb), hematocrit (HCT), RDW and erythrocyte parameters (mean corpuscular volume, MCV; mean cell hemoglobin, MCH; mean corpuscular hemoglobin concentration, MCHC) were assessed. DAS-28 was computed as measures of disease activity in our population. Results: The Study population was composed by 21 males and 45 females. Mean age of patients was 57±10 years. Mean disease duration was 5.5±6.9 years. The prevalence of subjects assuming DMARDs therapy was 46%, whereas the percentage of subjects assuming biologic agents were 36%. Patients showed overall normal levels of Hb (14±1.2 g/L), HCT (42.9±4.1%) and red blood cells parameters (MCV: 88.7±5.9 fL; MCH: 29.1±2.2 pg; MCHC: 32.6±1.0%). In univariate analysis, RDW was directly associated with CRP (r=0.25, p=0.04), ESR (r=0.24, p=0.05) and disease activity scores (DAS28-CRP: r=0.35, p=0.005; DAS28-ESR: r=0.34, p=0.009). Similar results were obtained in multiple regression analysis controlling for age, sex and disease duration as covariates. Conclusions: Our results suggest an interesting association between RDW and DAS 28 in rheumatoid arthritis. The mechanisms underlying this association are still unknown, but probably linked to the underlying inflammatory state and increased oxidative stress both correlated to impaired erythrocyte maturation. In our opinion, our data, if confirmed, might have important clinical implications. First of all, RDW might represent a useful marker for a better characterization of disease activity in RA, helping the clinician to define the more appropriate therapeutic strategy. Second RDW, a well-known predictor of adverse cardiovascular outcome, might provide additional information for cardiovascular risk stratification in RA, taking in account the high prevalence of cardiovascular events observed in this population. References: Tonelli M et al. Circulation. 2008;117:163-168 Lippi G et al. Arch Pathol Lab Med. 2009;133:628-32 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3729